A transplantable tumor model allowing investigation of NY-BR-1-specific T cell responses in HLA-DRB1*0401 transgenic mice - Das, Krishna; Eisel, David; Vormehr, Mathias; Müller-Decker, Karin; Hommertgen, Adriane; Jäger, Dirk; Zörnig, Inka; Feuerer, Markus; Kopp-Schneider, Annette; Osen, Wolfram; Eichmüller, Stefan B. (BMC cancer, 2019)
NY-BR-1 has been described as a breast cancer associated differentiation antigen with intrinsic immunogenicity giving rise to endogenous T and B cell responses. The current study presents the first murine tumor model allowing functional investigation of NY-BR-1-specific immune responses in vivo.
Gesehen am 30.10.2019